KONSEPSI PERENCANAAN ORGANISASI RUANG ISLAMI - Sri Puji Astuti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Public housing issue in Indonesia,  particularly in the urban area, has become a  widely discussed issue,  whether  related  to  land  limitation,  increasing  price,  or  the  developer  promises  that sometimes differ  from the existing facts. Whatever the problem is, the  housing requirements  for the predominantly Moslem population should be the major consideration, before other aspects are considered.    The  fact  is  that  this  matter  has  been  neglected  due  to  the  consideration  of  bigger people  needs.    Other  than  that,  the  highly  increasing  price  should  be  reconsidered  because  it  is related to purchasing power of the people. In other words, in the end, people do not always have an option to choose the best they think because at the same time they have to fulfill their basic needs. This writing attempts to provide an alternative concept that can be applied in creating a conducive housing  for  Moslem  families.  It  is  expected  that  this      concept  can  be  applied  in  the  general housing planning. Key words: rooms, housing, Moslem